APPLICATION OF TOUCHLESS METHODS FOR MAKING ENTRIES IN DENTAL RECORDS - O.P. GORBUNOVA; V.V. BORISOV; A.V. TIMOSHIN; S.D. DANSHINA (Avicenna Tajik State Medical University, 2023)
This review focuses on the current issues of asepsis in dental settings and ways to prevent contact infection using touchless methods of making entries in dental records. Contact transmission is the main route of microbial contamination in dentistry. Various environmental surfaces in dental settings are difficult to disinfect, while contact with the staff's hands with the surfaces of computer equipment is inevitable. Continuous disinfection of the components of the computer hardware in the dental unit can cause damage and significantly reduce their useful life. The disinfection of the keyboard, touch screens, as well as other devices for entering dental records, is especially challenging. Alternative touchless methods for operating computers by dentists and nurses are already applied in various dental settings, such as surgery units, where a high level of sterility is required during operation. The use of such methods not only reduces the time spent by the patient in the dental chair but also excludes the contact of the doctor's hands with hard-to-clean surfaces, minimizing the chance of contact infection transmission.